Properties of pineapple-leaf fibers after chemical treatments - Leesirisan, Siriwan (Bulletin of Applied Sciences, 2022)
This research studied properties of pineapple-leaf cellulose fibers after chemical treatments using various ratios of a mixture of sodium hydroxide and ethanol extracting solvent at 95°C and a treatment time duration between 2-4 hr. The treated fibers were then investigated using FTIR, TGA, XRD and SEM techniques. FTIR spectra indicated that non-cellulosic components were effectively eliminated. DTG thermograms showed that the temperature at the maximum weight loss of a treated fiber was closed to that of commercial available cellulose. In addition, XRD results indicated that the crystallinity index of the treated fiber was higher 56%, when compared to that of untreated fiber. Furthermore, SEM images revealed that the treated fibers were defibrillated from fiber bundles